Comparative osteology of the penguin‐like mid‐Cenozoic Plotopteridae and the earliest true fossil penguins, with comments on the origins of wing‐propelled diving. (29th June 2020) - Mayr, Gerald; Goedert, James L.; De Pietri, Vanesa L.; Scofield, R. Paul
Abstract: We compared the osteology of the late Eocene to early Miocene penguin‐like Plotopteridae from the North Pacific Basin with that of Paleocene stem group representatives of the Sphenisciformes and identified previously unrecognized similarities and differences. New data on the osteology of plotopterids, like the shape of the caudal end of the mandible, support a position of plotopterids outside the Suloidea, the clade formed by Sulidae, Phalacrocoracidae, and Anhingidae. However, as assumed by previous authors, the diving adaptations of plotopterids and sphenisciforms are likely to have evolved independently, and the resemblances in different parts of the postcranial skeleton therefore constitute one of the more striking examples of parallelism among tetrapods. We note that close relatives of both plotopterids and penguins forage by plunge diving. Whereas underwater locomotion of diving birds with a swimming ancestor is usually driven by the feet, we hypothesize that plotopterids and other wing‐propelled divers are more likely to have had volant ancestors that initiated diving by shallow plunges into the sea. Abstract : Coracoids (a, b) and tarsometatarsi (c, d) of species of the penguin‐like Plotopteridae (a, c) and Paleocene stem group Sphenisciformes (b, d). The extinct Plotopteridae occurred in the North Pacific and evolved a striking skeletal resemblance to penguins. In the article, the osteology of plotopterids and the earliest known fossil penguins is for the first time compared in detail.